Multiple Temporalities in Personal Information Management - McKenzie, Pam; Davies, Elisabeth (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2016)
Multiple temporalities are negotiated locally according to socially situated priorities. Classifying, documenting, and coordinating multiple temporalities is an important aspect of personal information management. This paper analyzes temporal aspects of personal information management work. Des temporalités multiples sont négociées localement en fonction de priorités socialement situées. Classer, documenter, et coordonner des temporalités multiples est un aspect important de la gestion des renseignements personnels. Cette étude analyse les aspects temporels du travail de gestion des renseignements personnels.